Equivalence of many photon green functions in DKP and KGF statistical quantum field theories - Fainberg, Vladimir Yakovlevich (2004)
We prove the equivalence of many-photon Green functions in statistical quantum field Duffin-Kemmer-Petiau (DKP) and Klein-Gordon- Fock (KGF) theories using functional path integral formalism for partition functional in statistical quantum (finite temperature) field theory. We also calculate the polarization operators in these theories in oneloop approximation, and demonstrate their coincidence.